Perubahan Tingkat Pengetahuan Cuci Tangan Pakai Sabun setelah Pendidikan Kesehatan dengan Pendekatan Edukatif - Indah Sundawati; Abi Muhlisin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to evaluate the effectiveness of health education using an educational approach in increasing public knowledge regarding handwashing with soap (CTPS). The method used was a pre-experimental design with a one-group pre-test and post-test approach without a control group. The results showed an increase in the mean knowledge score of respondents from 10.27 in the pre-test to 14.40 in the post-test. Statistical analysis showed a t-value of -7.059 with a significance value of p = 0.001 (p < 0.05), indicating a statistically significant difference between knowledge levels before and after health education. In conclusion, health education using an educational approach, implemented in a structured and participatory manner, can increase public knowledge regarding handwashing with soap and can be an effective promotional strategy to support the sustainable implementation of clean and healthy living behaviors in the community. Keywords: Handwashing with Soap, Health Education, Clean and Healthy Living Behavior